Effect of globalisation on children's mental health. Issue 7507 (30th June 2005) - Timimi, Sami
Abstract : Globalisation is resulting in inappropriate domination of the Western view of mental health as well as of economic approaches. Western child psychiatrists have much to learn from child rearing practices in other countries